Variation among subspecialists in the diagnosis of urinary tract infection in children with neurogenic bladders. Issue 6 (December 2018) - Forster, C.S.; Jackson, E.; Goldstein, S.L.
Summary: Background: Children with neurogenic bladders who require clean intermittent catheterization (CIC) frequently have bacteriuria. However, there is no consensus on what constitutes at urinary tract infection (UTI) in this population. Multiple subspecialists are often involved in the management of these patients, although they are frequently cared for by hospitalists when admission is required. Objective: The objective of this study was to describe the variability in opinion between subspecialists in the diagnosis of a UTI in CIC-dependent children. Study design: A scenario-based survey was distributed to physicians in the divisions of urology, nephrology, and hospital medicine at a single free-standing children's hospital. Respondents rated their degree of confidence on whether a specific scenario represented UTI or colonization on an 11-point Likert Scale. Median responses were compared with the Kruskal–Wallis test with pair-wise comparisons. Results: Back/flank pain, abdominal pain, and vomiting were the most common symptoms that were suggestive of a UTI in a non-febrile child. There was no single symptom chosen that was the most suggestive of a UTI in CIC-dependent child. There was significant variability between specialists in the diagnosis of UTI in specific clinical scenarios on the survey. Hospitalists were significantly less confident about the diagnosis of a UTI than urologists in two of the clinical scenarios. Conclusions: Standardization and implementation of consensus criteria for UTI in this high-risk population is needed. Summary Figure Responses to various clinical scenarios in which respondents were asked to rank how confident they were that the scenario represented either colonization or infection. On this scale, 0 = I am confident this is colonization, 5 = Colonization and infection are equally possible, 10 = I am confident this represents an infection.